The Organizational learning in the impress medium editor companies. Case: company "Al Dia Con La Noticia C.A" (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The research had as finalit, evaluate the "Al Dia Con La Noticia, C.A" company management model, under the theoretical lineaments of the Organizational Learning. The research done was of field, descriptive type and transversal and supported on documental sources. Because is a Case of Study type investigation, the population concept was represented for all the organization. To collect the information it was applied a questionnaire to twenty (20) key informants, and reinforced with the direct observation, in the same way was complemented the getting of information with the application of a semi structured interview, composed of six items were came out new questions in the course of the research dynamic. It was a quantitative investigation. The instruments were under subject by the expert's judgment. Concluding, can affirm that the company is qualify as a organization in learning process, which management process in the acknowledge management, still presents obstacles in its purpose of manage the organizational learning, which thanks to its human capital could achieve in relatively short terms.
Keywords: knowledge management; organizational learning; human capital